Characterization of a GM7 glioblastoma cell line showing CD133 positivity and both cytoplasmic and nuclear localization of nestin - Loja, Tomas; Chlapek, Petr; Kuglik, Petr; Pesakova, Martina; Oltova, Alexandra; Cejpek, Pavel; Veselska, Renata (Oncology reports, 2009)
A newly established GM7 cell line was derived from the tumor tissue of a 65-year-old man surgically treated for a relapse of glioblastoma multiforme that occurred 10 months after first surgery following radiotherapy. GM7 cells exhibit spindle or glia-like morphology, and multinucleated giant cells are also present in the culture. The cells proliferate rapidly (PDT is about 18 h) and tend to grow in multilayer without contact inhibition. Using G-banding and SKY, the GM7 cell line was identified as near-triploid with a large number of structural and numerical abnormalities. Repeated karyotyping during long-term cultivation confirmed a chromosome number of 70+/-3 chromosomes per cell. Special attention was paid to the immunocytochemical analysis of protein markers in this cell line; GM7 cells showed strong positivity for CD133, vimentin, nestin, NF-160 and S-100 protein and weak positivity for GFAP and NSE, but were negative for synaptophysin. The most important features of the GM7 cell line are its stable phenotype CD133+/nestin+, which are accepted as stem cell markers in neural stem/progenitor cells, and especially unusual intracellular localization of the IF protein nestin, which was detected and repeatedly confirmed both in the cytoplasm and cell nucleus. For this reason, the new GM7 glioblastoma cell line represents an important model suitable not only for further studies on glioblastoma biology and cancer stem cells, but particularly for the detailed investigation of the role of nestin in transformed cells.
Keywords: senioři; Glycoproteins; nádorové buněčné linie; buněčné jádro; průtoková cytometrie; Glioblastoma; imunohistochemie; mužské pohlaví; Nestin; transmisní elektronová mikroskopie; AC133 Antigen; Cell Line, Tumor; glioblastom; Nerve Tissue Proteins; western blotting; Biomarkers, Tumor; Flow Cytometry; Peptides; Blotting, Western; Cell Nucleus; Immunohistochemistry; cytoplazma; nádorové biomarkery; Humans; fluorescenční protilátková technika; Antigens, CD; Microscopy, Electron, Transmission; Intermediate Filament Proteins; proteiny nervové tkáně; Chromosome Aberrations; chromozomální aberace; peptidy; Fluorescent Antibody Technique; Cytoplasm; glykoproteiny; antigen AC133; proteiny intermediálních filament; nestin; Aged; CD antigeny; lidé; Male